Preparation method of reinforced composite wood floor using low formaldehyde adhesive

CN120645289BActive Publication Date: 2026-10-30JIUSHENG WOOD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510878150.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-26
Publication Date
2026-10-30
Estimated Expiration
2045-06-26

AI Technical Summary

Technical Problem

[0006]本发明的目的是提供一种采用低甲醛胶黏剂的强化复合木地板制备方法,旨在解决现有复合木地板甲醛释放量高、功能单一、环保性提升空间有限、表面耐久性不足以及对室内微气候调控能力弱等技术问题

Benefits of technology

通过使用生物基多元复合胶黏剂,大幅降低了地板的甲醛释放量,使产品甲醛释放量控制在0.1mg/L以下,远低于E0级标准要求,显著提高了产品的环保性能;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120645289B_ABST
    Figure CN120645289B_ABST
Patent Text Reader

Abstract

The application discloses a kind of reinforced composite wood floor preparation methods using low formaldehyde adhesive, comprising: urea-formaldehyde resin, lignin, chitosan and soybean protein isolate are mixed to prepare bio-based multivariate composite adhesive;The adhesive is mixed with wood fiber and bamboo fiber and added to prepare base material blank microencapsulated phase change material;Base material blank is segmented and is formed by heat pressing;Photocatalytic type formaldehyde capture primer is coated on the surface of base material;Multifunctional wear-resistant layer containing self-repairing microcapsule, super-hydrophobic nanomaterial and negative ion release material is prepared;Functional base material is secondarily hot-pressed with decorative paper and wear-resistant layer.The reinforced composite wood floor prepared by the application has low formaldehyde emission, good temperature regulation function, surface self-repairing, stain-repellent self-cleaning, air purification and other functions, meets the needs of healthy, comfortable, smart home environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of wood composite material manufacturing technology, specifically to a method for preparing reinforced composite wood flooring using low-formaldehyde adhesives. This invention is particularly applicable to the preparation process of environmentally friendly, multifunctional composite wood flooring for interior decoration materials, and can be widely used in residential homes, commercial spaces, medical institutions, and other places with high requirements for indoor environmental quality. Background Technology

[0002] As an important component of interior decoration materials, composite wood flooring's environmental performance and functional characteristics directly impact indoor environmental quality and resident health. With increasing demand for healthy living, low-formaldehyde-emission and multifunctional composite wood flooring has become a key direction for industry development.

[0003] Currently, most composite wood flooring on the market uses urea-formaldehyde resin as an adhesive. The substrate is prepared by mixing wood fiber raw materials with the adhesive through a hot-pressing process, and then a decorative layer and a wear-resistant layer are laminated together. To reduce formaldehyde release, some manufacturers use modified urea-formaldehyde resin or add formaldehyde scavengers to control the formaldehyde emission of their products within national standards.

[0004] Existing low-formaldehyde composite wood flooring manufacturing technologies mainly involve modifying urea-formaldehyde resin with bio-based materials such as lignin and chitosan, coating the substrate surface with a primer containing formaldehyde scavenging agents, and then hot-pressing it under specific temperature and pressure conditions. Although this method can control formaldehyde emissions below the E0 standard (≤0.3mg / L) and ensure basic mechanical properties, it still has significant technical limitations.

[0005] However, this traditional process suffers from limitations such as single function, limited room for improvement in environmental friendliness, passive role in environmental regulation, insufficient surface durability, and weak ability to control indoor microclimate. In particular, the adhesive used in traditional processes is still mainly urea-formaldehyde resin, and there is a lack of consideration for advanced functions such as active temperature and humidity regulation, self-cleaning, and air purification, which fails to meet the needs of modern consumers for a healthy, comfortable, and intelligent home environment. Summary of the Invention

[0006] The purpose of this invention is to provide a method for preparing reinforced composite wood flooring using low-formaldehyde adhesives, aiming to solve the technical problems of existing composite wood flooring such as high formaldehyde emission, single function, limited room for improvement in environmental protection, insufficient surface durability, and weak ability to regulate indoor microclimate.

[0007] To achieve the above objectives, the technical solution provided by the present invention is as follows: A method for preparing reinforced composite wood flooring using low-formaldehyde adhesives includes the following steps: Urea-formaldehyde resin, lignin, chitosan and soy protein isolate are mixed and reacted at 60-70℃ for 90-120 minutes to obtain a bio-based multi-component composite adhesive. Wood fiber and bamboo fiber are mixed with the bio-based multi-component composite adhesive at a dry weight ratio of 8:1-10:1, microencapsulated phase change material is added, and the mixture is mixed for 10-15 minutes using a high-speed mixer to obtain a substrate blank with phase change energy storage function. The substrate blank is subjected to segmented hot pressing molding at a temperature of 175-185℃ and a pressure of 28-32MPa for 16-19 minutes to obtain a phase change energy storage temperature regulation substrate plate. A photocatalytic formaldehyde-capturing primer containing nano-titanium dioxide and modified zeolite is coated on the surface of the substrate, and after drying, a surface-functionalized substrate is obtained. A UV-curable coating containing self-healing microcapsules, superhydrophobic nanomaterials and negative ion releasing materials is applied to decorative paper and then cured by UV light to obtain a multifunctional wear-resistant layer. The surface-functionalized substrate is laminated with decorative paper and the multifunctional wear-resistant layer, and then hot-pressed for 3-5 minutes at a temperature of 155-165℃ and a pressure of 3.5-4.5MPa to obtain low-formaldehyde reinforced composite wood flooring.

[0008] Preferably, urea-formaldehyde resin, lignin, chitosan, and soy protein isolate are mixed and reacted at 60-70°C for 90-120 minutes to obtain a bio-based multi-component composite adhesive, comprising: The pH of the urea-formaldehyde resin is pre-adjusted to 8.0-8.5, the lignin is sulfonated, the chitosan is dissolved in 1%-2% acetic acid solution to prepare a colloidal solution, and the soy protein isolate is dissolved under alkaline conditions at pH 9-10 to obtain the pretreated components. The pretreated components include the pretreated urea-formaldehyde resin, lignin, chitosan, and soy protein isolate. The pretreated components were mixed in a reactor at a weight ratio of 50:12-15:3-5:25-30 for urea-formaldehyde resin, lignin, chitosan, and soy protein isolate. The mixture was stirred mechanically at 200-300 rpm, and the pH was maintained in the range of 7.5-8.5. 0.5%-1% ammonium chloride was added as a curing catalyst to obtain a preliminary composite adhesive. Add 3%-5% polyfunctional isocyanate as a crosslinking agent and 0.5%-1% polyvinyl alcohol as a stabilizer to the preliminary composite adhesive, and continue to react at 65°C for 30-45 minutes to obtain the bio-based multi-component composite adhesive.

[0009] Preferably, the addition of microencapsulated phase change materials includes: n-Alkanes with a phase change temperature of 28-32℃ were selected as the core material, and microencapsulation was carried out using in-situ polymerization with polyurethane as the wall material. The average particle size of the microcapsules was controlled to be 10-20μm to obtain microencapsulated phase change materials. Based on the mixture of the bio-based multi-component adhesive with wood fiber and bamboo fiber, the microencapsulated phase change material is added to it at a ratio of 8%-12% of the total dry weight of the fiber and adhesive, and mixed for 10-15 minutes using a high-speed mixer to obtain the substrate blank containing phase change energy storage function.

[0010] Preferably, the substrate blank is subjected to segmented hot pressing, comprising: The substrate blank is preheated by gradually raising the temperature to 175°C and the pressure to 70% of the set value within the first 5 minutes to obtain a preheated blank. The preheated billet is subjected to a hot pressing treatment at a constant temperature of 175-185°C and a constant pressure of 28-32MPa for 9-12 minutes in the middle to obtain a preliminary shaped substrate. The preliminary molded substrate is cooled to 150°C and maintained under full pressure for shaping in the last 2-3 minutes to obtain the phase change energy storage temperature regulation substrate plate.

[0011] Preferably, the photocatalytic formaldehyde-capturing adhesive comprises: Using waterborne polyurethane dispersion as a base material, 3%-5% nano titanium dioxide, 1%-2% modified zeolite and 1%-3% activated carbon micro powder are added, along with 0.5%-1% silane coupling agent, to prepare the photocatalytic formaldehyde capture primer with a solid content of 30%-35%.

[0012] Preferably, a UV-curable coating containing self-healing microcapsules, superhydrophobic nanomaterials, and negative ion-releasing materials is applied to decorative paper and then UV-cured to obtain a multifunctional wear-resistant layer, comprising: Self-healing microcapsules with an average particle size of 3-5 μm were prepared by interfacial polymerization using dicyclopentadiene as the core material and polyurethane as the wall material, thus obtaining the self-healing component; Nanoscale silica particles with a particle size of 50-100 nm were synthesized by sol-gel method, and superhydrophobic nanomaterials were obtained by surface modification treatment with perfluorotridecyltriethoxysilane. Based on aliphatic polyurethane acrylate resin, 5%-8% of the self-healing component, 2%-4% of the superhydrophobic nanomaterial, 4%-6% of tourmaline micro powder and 3%-5% of nano alumina are added, and 2%-3% of photoinitiator is added to obtain a UV-curable coating containing multifunctional components. The UV-curable coating containing the multifunctional components was applied to decorative paper, with the wet coating thickness controlled at 40-50 μm, at a wavelength of 365 nm and a power density of 300-400 mW / cm².2 Curing under UV-A irradiation for 30-60 seconds yields a pre-cured multifunctional wear-resistant layer; The thickness of the initially cured multifunctional wear-resistant layer is controlled to ensure that the final thickness is 30-40μm, thus obtaining the multifunctional wear-resistant layer.

[0013] Preferably, the self-healing microcapsules are prepared using interfacial polymerization, comprising: The dicyclopentadiene was mixed with Grubbs catalyst as a core material and dispersed in an aqueous phase to form an emulsion, thus obtaining a core material emulsion. Polyurethane prepolymer monomers are added to the core material emulsion, and polyurethane wall material is formed on the surface of the core material through interfacial polymerization to obtain the self-healing microcapsules.

[0014] Preferably, the surface-functionalized substrate is laminated with decorative paper and the multifunctional wear-resistant layer, and then subjected to a second hot-pressing process for 3-5 minutes at a temperature of 155-165℃ and a pressure of 3.5-4.5MPa, including: The decorative paper is precisely positioned on the surface functionalized substrate, and the multifunctional wear-resistant layer is covered on the decorative paper to form a laminated structure, thus obtaining a pre-laminated body. The pre-assembled body is heated in stages, with a rate of 5-8℃ / min to 155-165℃ and pressure maintained, and then the temperature is controlled to drop below 80℃ before the pressure is released to obtain the low-formaldehyde reinforced composite wood flooring.

[0015] Preferably, it further includes: integrating an active environmental control function into the low-formaldehyde reinforced composite wood flooring: Select a specific surface area ≥ 1500 m² 2 / g of activated carbon fiber felt was used to grow graphene nanosheets on its surface by chemical vapor deposition to obtain an activated carbon fiber / graphene composite adsorption layer. Based on the conductive properties of the activated carbon fiber / graphene composite adsorption layer, carbon nanotube conductive ink is printed on a polyimide film substrate to form a matching electrothermal film, and the surface resistance is controlled at 10-20Ω to obtain an electrothermal regeneration module. Based on the working requirements of the electrothermal regeneration module, a temperature and humidity sensor, a VOC sensor, and a temperature sensor are integrated, and the module communicates with the control unit via Bluetooth Low Energy protocol to obtain a sensor system that matches the regeneration module. The activated carbon fiber / graphene composite adsorption layer, the electrothermal regeneration module, and the sensor system are integrated into a functional module and installed in a reserved space at the bottom of the substrate of the low formaldehyde reinforced composite wood flooring to obtain reinforced composite wood flooring with active environmental regulation function.

[0016] The beneficial effects of this invention are: By using bio-based multi-component adhesives, the formaldehyde emission of the flooring is significantly reduced, keeping the formaldehyde emission of the product below 0.1 mg / L, which is far below the E0 standard requirement and significantly improves the environmental performance of the product. By adding microencapsulated phase change materials to the substrate, the floor can be given a temperature regulation function, which can effectively reduce the temperature fluctuation of the floor surface by 1-3℃ and improve indoor thermal comfort. By integrating self-healing microcapsules, superhydrophobic nanomaterials, and negative ion releasing materials into the wear-resistant layer, the flooring is equipped with scratch self-healing, stain-resistant self-cleaning, and air purification functions, which significantly improves the product's service life and functionality. By using a photocatalytic formaldehyde-capturing adhesive, the continuous capture and decomposition of indoor formaldehyde is achieved, further enhancing the product's air purification capabilities. By integrating an active environmental control system, the flooring is equipped with the ability to actively adsorb and control the regeneration of harmful substances such as VOCs in the room, breaking through the limitations of traditional flooring's passive environmental protection. Attached Figure Description

[0017] To more clearly illustrate the technical solutions of the embodiments of this disclosure, the accompanying drawings used in the embodiments will be briefly described below. These drawings are incorporated in and constitute a part of this specification. They illustrate embodiments conforming to this disclosure and, together with the specification, serve to explain the technical solutions of this disclosure. It should be understood that the following drawings only show some embodiments of this disclosure and should not be considered as limiting the scope. Those skilled in the art can obtain other related drawings based on these drawings without creative effort.

[0018] Figure 1 This is a flowchart illustrating the preparation process of the bio-based multi-component composite adhesive in this embodiment of the invention. Figure 2 This is a process flow diagram of the preparation process of the phase change energy storage temperature regulation substrate in an embodiment of the present invention; Figure 3 This is a graph showing the process parameters of the segmented hot pressing molding process in an embodiment of the present invention. Figure 4 This is a flowchart of the substrate surface functionalization process in an embodiment of the present invention; Figure 5 This is a flowchart illustrating the process for preparing the multifunctional wear-resistant layer in an embodiment of the present invention. Figure 6 This is a schematic cross-sectional view of the reinforced composite wood flooring structure in an embodiment of the present invention. Detailed Implementation

[0019] To make the objectives, technical solutions, and advantages of the embodiments of this disclosure clearer, the technical solutions of the embodiments of this disclosure will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this disclosure, and not all of them. The components of the embodiments of this disclosure described and shown in the accompanying drawings can generally be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of this disclosure provided in the accompanying drawings is not intended to limit the scope of the claimed disclosure, but merely represents selected embodiments of this disclosure. All other embodiments obtained by those skilled in the art based on the embodiments of this disclosure without inventive effort are within the scope of protection of this disclosure.

[0020] It should be noted that similar labels and letters in the following figures indicate similar items. Therefore, once an item is defined in one figure, it does not need to be further defined and explained in subsequent figures.

[0021] In this document, the term "and / or" merely describes a relationship, indicating that three relationships can exist. For example, A and / or B can represent three cases: A alone, A and B simultaneously, and B alone. Furthermore, the term "at least one" in this document means any combination of at least two of any one or more elements. For example, including at least one of A, B, and C can mean including any one or more elements selected from the set consisting of A, B, and C.

[0022] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0023] This application provides a method for preparing reinforced composite wood flooring using a low-formaldehyde adhesive, comprising the following steps: S1 mixes urea-formaldehyde resin, lignin, chitosan and soy protein isolate, and reacts them at 60-70℃ for 90-120 minutes to obtain a bio-based multi-component composite adhesive. S2 mixes wood fiber and bamboo fiber with the bio-based multi-component composite adhesive at a dry weight ratio of 8:1-10:1, adds microencapsulated phase change material, and mixes for 10-15 minutes using a high-speed mixer to obtain a substrate blank with phase change energy storage function. S3 performs segmented hot pressing on the substrate blank, hot pressing for 16-19 minutes at a temperature of 175-185℃ and a pressure of 28-32MPa to obtain a phase change energy storage temperature regulation substrate plate. S4 Coats the surface of the substrate with a photocatalytic formaldehyde-capturing primer containing nano-titanium dioxide and modified zeolite, and after drying, obtains a surface-functionalized substrate. S5 applies a UV-curable coating containing self-healing microcapsules, superhydrophobic nanomaterials, and negative ion releasing materials onto decorative paper, and then performs UV curing to obtain a multifunctional wear-resistant layer. S6 The surface-functionalized substrate is laminated with decorative paper and the multifunctional wear-resistant layer, and then hot-pressed for 3-5 minutes at a temperature of 155-165℃ and a pressure of 3.5-4.5MPa to obtain low-formaldehyde reinforced composite wood flooring.

[0024] The steps described above will be explained in detail below: S1: Preparation of Bio-based Multi-component Composite Adhesives like Figure 1 As shown, the preparation of bio-based multi-component composite adhesives includes four main steps: raw material pretreatment, composite adhesive preparation, adhesive modification and stabilization, and performance testing and adjustment.

[0025] First, raw material preparation and pretreatment were carried out: urea-formaldehyde resin (48% solid content), liquid sulfonated lignin (55% solid content), chitosan powder (molecular weight 300,000), and soy protein isolate (92% protein content) were pretreated separately. Specifically, the pH of the urea-formaldehyde resin was adjusted to 8.2 using sodium hydroxide solution; the liquid lignin was sulfonated to enhance its water solubility and activity; chitosan was dissolved in a 1.5% acetic acid solution to prepare a colloidal solution; and soy protein isolate was dissolved under alkaline conditions at pH 9.5 to open up the protein structure and expose more active sites.

[0026] The composite adhesive was then prepared: The pretreated components (urea-formaldehyde resin, lignin, chitosan, and soy protein isolate) were mixed in a reactor at a weight ratio of 50:14:4:28. The mixture was mechanically stirred at 250 rpm for 105 minutes at 65°C, with the pH maintained at 8.0 using sodium hydroxide solution. 0.8% ammonium chloride was added as a curing catalyst during the reaction, with the addition amount controlled to be 0.8% of the urea-formaldehyde resin mass.

[0027] Next, the adhesive was modified and stabilized: 4% polyfunctional isocyanate (MDI) was added to the reaction system as a crosslinking agent to strengthen the crosslinking network structure of the adhesive and improve water resistance and bonding strength. Simultaneously, 0.8% polyvinyl alcohol was added as a thickener and stabilizer to improve the rheological properties and storage stability of the adhesive. After thorough mixing, the reaction was continued at 65°C for 40 minutes to form a stable bio-based multi-component composite adhesive.

[0028] Finally, the adhesive performance was tested and adjusted: the tested adhesive had a solid content of 50%, a viscosity of 10000 mPa·s, a pH of 7.3, and a gel time of 75 seconds (at 100℃). The test results show that the prepared bio-based multi-component composite adhesive meets the process requirements for subsequent substrate preparation.

[0029] S2: Preparation of phase change energy storage temperature regulation substrate like Figure 2 As shown, the preparation of phase change energy storage temperature regulation substrate includes four main steps: preparation and treatment of fiber raw materials, preparation of microencapsulated phase change materials, material mixing, and pre-pressing and curing.

[0030] First, the fiber raw materials are prepared and processed: wood fiber (70%) and bamboo fiber (30%) are selected as the base material. The fiber raw materials are dried to control the moisture content within 4%. Through a screening process, particles with a fiber size of 0.5-2mm are selected to ensure uniform fiber size, which is beneficial for thorough mixing with the adhesive and the formation of a stable structure.

[0031] Then, microencapsulated phase change materials were prepared: n-alkane (eicosane C20H42) with a phase change temperature of 30℃ was selected as the core material, and microencapsulated phase change materials (MicroPCMs) were prepared by in-situ polymerization with polyurethane as the wall material. The average particle size of the microcapsules was controlled to be 15 μm, and the mass ratio of wall material to core material was 1:4.5 to ensure that the microcapsules had sufficient mechanical strength and thermal stability. The prepared MicroPCMs had a latent heat of phase change of 185 J / g and thermal stability that could withstand short-term heating at 190℃.

[0032] Next, the fiber material, adhesive, and phase change material were mixed: the treated fiber raw material was mixed with the bio-based multi-component composite adhesive prepared in Example 1 at a dry weight ratio of 9:1, and MicroPCMs were added at an amount of 10% of the total dry weight of the fiber and adhesive. The mixture was stirred in a high-speed mixer at 250 rpm for 12 minutes to ensure that the three materials were uniformly dispersed, forming a substrate blank containing PCMs.

[0033] Finally, the substrate blank is pre-pressed and cured: the uniformly mixed substrate blank is pre-pressed at room temperature and a pressure of 2 MPa for 2.5 minutes to form a pre-formed blank blanket. The pre-pressed blank blanket is then cured for a short time (15 minutes at room temperature) to ensure that the adhesive and fibers are in full contact, thereby improving the efficiency and quality of subsequent hot pressing.

[0034] S3: Hot pressing of substrate like Figure 3 As shown, the hot pressing of the substrate includes four main steps: hot pressing parameter optimization setting, hot pressing process control, substrate cooling and humidity conditioning, and substrate quality inspection.

[0035] First, the hot pressing parameters were optimized: Based on the characteristics of the blank blanket prepared in Example 2, the hot pressing parameters were set as follows: hot pressing temperature 180℃; pressure 30MPa; hot pressing time 18 minutes. Simultaneously, a segmented hot pressing curve was designed: for the first 5 minutes, the temperature gradually increased to 175℃, and the pressure was 70% of the set value; for the middle 10 minutes, constant temperature and pressure were maintained; and for the last 3 minutes, the temperature was reduced to approximately 150℃ while maintaining full pressure, thus forming an ideal density gradient distribution.

[0036] Then, the hot pressing process is controlled: the blank blanket is placed between the plates of the hot press, and edge limiters are installed to control the plate thickness (10mm). The hot pressing program is started, and the set hot pressing parameters are executed. During the hot pressing process, the hot pressing conditions are monitored in real time by pressure and temperature sensors to ensure that the entire hot pressing process is stable and controllable. During the hot pressing process, PCMs undergo a controllable phase change process, in which part of the microcapsule core material melts while the wall material remains intact.

[0037] Next, the substrate is cooled and conditioned: After hot pressing, the substrate is transferred to a cooling rack, where forced air cooling is used to lower the temperature to below 40°C. The cooled substrate is then transferred to a conditioned chamber and conditioned for 36 hours at 23°C and 62% relative humidity to stabilize the moisture content at 8%, reducing dimensional changes during subsequent processing and use.

[0038] Finally, the substrate quality is tested: the conditioned substrate is tested for quality, including a density of 900 kg / m³. 3 The substrate material exhibits the following properties: moisture content of 8%, thickness expansion rate of 10.5% (after 24 hours of immersion), static bending strength of 38 MPa, internal bond strength of 0.65 MPa, and formaldehyde release of 0.08 mg / L. The uniformity of PCMs distribution within the substrate was assessed using an infrared thermal imager to ensure consistent temperature control performance. The test results indicate that the prepared phase change energy storage temperature-regulating substrate meets the required quality standards.

[0039] s4: Substrate surface functionalization treatment like Figure 4 As shown, the functionalization treatment of the substrate surface includes four main steps: substrate surface pretreatment, preparation of photocatalytic formaldehyde capture primer, coating and drying of primer, and performance testing of primer layer.

[0040] First, the substrate surface is pretreated: the substrate surface output from Example 3 is sanded using 150-grit sandpaper to remove surface dust and burrs, ensuring surface smoothness. High-pressure airflow is used to remove dust after sanding, and then isopropyl alcohol is used to wipe the surface to remove oil stains, improve surface wettability and coating uniformity.

[0041] Then, the photocatalytic formaldehyde-capturing primer was prepared: using an aqueous polyurethane dispersion as the base material, 4% nano-titanium dioxide (particle size 20nm, a mixture of anatase and rutile types, specific surface area 280m²) was added. 2 / g) was used as a photocatalyst. Simultaneously, 1.5% modified zeolite (silver ion exchange zeolite) and 2% activated carbon powder were added as adsorbents. 0.8% silane coupling agent was added to improve the compatibility between the filler and polyurethane, and appropriate amounts of defoamer and leveling agent were added to prepare a functional primer with a solid content of 32%.

[0042] Next, the primer is applied and dried: the prepared functional primer is evenly applied to the treated substrate surface using a roller coating method, with the coating amount controlled at 110 g / m². 2 (Wet weight). The coated substrate is placed in a tunnel drying equipment and dried at 65°C for 12 minutes to fully cure the primer and form a functional primer layer with a thickness of 28μm.

[0043] Finally, the performance of the primer layer was tested: the adhesion was 2.2 MPa, the formaldehyde capture efficiency was 88% (capture rate of 1.0 mg / L formaldehyde under standard test conditions), and the photocatalytic activity was 55% / 24h (degradation rate of formaldehyde under standard visible light irradiation conditions). The test results indicate that the primer layer adheres firmly to the substrate and has excellent formaldehyde capture and decomposition capabilities.

[0044] s5: Preparation of multifunctional wear-resistant layer like Figure 5 As shown, the preparation of the multifunctional wear-resistant layer includes four main steps: preparation of self-healing microcapsules, preparation of superhydrophobic / oleophobic nanomaterials, formulation of multifunctional UV-curable coatings, and coating and curing of the multifunctional wear-resistant layer.

[0045] First, self-healing microcapsules were prepared: self-healing microcapsules containing dicyclopentadiene (DCPD) and Grubbs catalyst were prepared using interfacial polymerization. DCPD and Grubbs catalyst were mixed as the core material and dispersed in an aqueous phase to form an emulsion. Polyurethane prepolymer monomers were added to the core material emulsion, and a polyurethane wall material was formed on the core material surface through interfacial polymerization, yielding self-healing microcapsules with an average particle size of 4 μm. The microcapsules possess sufficient mechanical strength to rupture and release the repair agent when the wear-resistant layer is scratched, but remain stable during normal UV curing.

[0046] Then, the superhydrophobic / oleophobic nanomaterials were prepared: nano-sized silica particles (80 nm in diameter) were synthesized using the sol-gel method, and their surface was modified with perfluorotridecyltriethoxysilane to impart superhydrophobic / oleophobic properties. The modified nanoparticles exhibited good dispersibility, with a water contact angle of 155° and an oil contact angle of 125°, ensuring excellent antifouling and self-cleaning properties for the wear-resistant layer.

[0047] Next, a multifunctional UV-curable coating was formulated: using aliphatic polyurethane acrylate as the main resin (65% of total solids), 6% self-healing microcapsules, 3% superhydrophobic nanomaterials, and 5% tourmaline micropowder (2μm particle size, capable of continuously releasing negative ions) were added. 4% nano-alumina was added as a wear-resistant reinforcing agent, 2.5% photoinitiator (a mixture of Irgacure 184 and Irgacure 819), and 1.5% leveling agent and defoamer. The mixture was thoroughly mixed using a high-speed disperser to prepare a UV-curable coating with a solids content of 96%.

[0048] Finally, the multifunctional wear-resistant layer is coated and cured: using precision coating equipment, the prepared UV-curable coating is evenly applied to the decorative paper, controlling the wet coating thickness to 45μm. Immediately after coating, it enters the UV curing system at UV-A (wavelength 365nm, power density 350mW / cm²). 2 After curing under irradiation for 45 seconds, a multifunctional wear-resistant layer with a thickness of 35μm is formed. The cured wear-resistant layer has high transparency and good self-healing properties, superhydrophobic properties, and negative ion release function.

[0049] s6: Composite laminate of flooring like Figure 6 As shown, the composite lamination of flooring includes five main steps: processing and positioning of decorative paper, stacking and pre-pressing of multi-functional layers, secondary hot-pressing lamination, edge treatment and dimensional processing, and finished product inspection and packaging.

[0050] First, the decorative paper is processed and positioned: select high-quality decorative paper with a lightfastness rating of 6 or higher (weight 90g / m²). 2 The paper is pre-impregnated with melamine resin, with the resin content controlled at 110% (relative to the weight of the paper). The decorative paper is then precisely positioned on the surface-functionalized substrate output in Example 4, ensuring that the pattern is aligned with the edges of the substrate, free of bubbles and wrinkles.

[0051] Then, the multifunctional layers are laminated and pre-pressed: the multifunctional wear-resistant layer (along with the decorative paper) prepared in Example 5 is precisely covered on the functionalized substrate to form a laminated structure of "substrate-base adhesive-decorative paper-wear-resistant layer". Vacuum adsorption is used to remove interlayer air bubbles to ensure that each layer is tightly bonded. Short-term pre-pressing (at room temperature, pressure 0.8 MPa, time 45 seconds) is performed to further ensure the stability of the laminated structure, resulting in a pre-laminated body.

[0052] Next, a second hot-pressing process is performed: the pre-assembled material is transferred to a hot press, and the temperature is increased in stages at a rate of 6℃ / min to 160℃. It is then hot-pressed for 4 minutes under a pressure of 4MPa. The temperature is then controlled to drop below 80℃ before the pressure is released to avoid warping and deformation caused by temperature stress, resulting in low-formaldehyde reinforced composite wood flooring.

[0053] Next, edge treatment and dimensional processing are performed: the edges of the hot-pressed floorboards are sawn to ensure dimensional accuracy. According to the connection requirements, a locking mechanism is fabricated with dimensions of 1220mm × 180mm × 12mm. The processed floorboards are then placed in a humidity-regulating chamber and equilibrated for 36 hours at 22℃ and 55% relative humidity to stabilize the overall moisture content at 7.5%.

[0054] Finally, finished product inspection and packaging are carried out: A comprehensive quality inspection is conducted on the finished flooring, including: appearance quality (no bubbles, delamination, damage, or other defects), dimensional accuracy (length and width error 0.15mm, thickness error 0.08mm), surface performance (abrasion resistance 6500 revolutions, scratch resistance 3.8N, stain resistance level 5), and physical properties (static bending strength 38MPa, impact elasticity 14%, formaldehyde emission 0.08mg / L). After passing inspection, the flooring is packaged with moisture protection and prepared for shipment.

[0055] This application also includes s7: integration of active environmental control systems. The integration of the active environmental control system includes five main steps: preparation of activated carbon fiber / graphene composite adsorption layer, design and preparation of electrothermal regeneration module, integration of sensor system, structural design and assembly of system, and control system and intelligent algorithm.

[0056] First, the activated carbon fiber / graphene composite adsorption layer was prepared: a specific surface area of ​​1800 m² was selected. 2 A 1.5 mm thick activated carbon fiber mat was used as the basic adsorbent. Graphene nanosheets were grown on the surface of the activated carbon fiber using chemical vapor deposition (CVD) to improve conductivity and adsorption selectivity. The prepared composite material exhibits excellent adsorption capacity for formaldehyde and VOCs (formaldehyde adsorption capacity 55 mg / g) and good conductivity (resistivity 8 Ω·cm), facilitating subsequent electrothermal regeneration.

[0057] The electrothermal regeneration module was then designed and fabricated: Flexible printed circuit technology was used to print carbon nanotube conductive ink onto a polyimide (PI) film substrate (0.15 mm thick), forming a mesh-like electrothermal film. The sheet resistance of the electrothermal film is 15 Ω, and it can uniformly heat to 60°C when a 12V DC current is applied. An insulating protective layer is coated on the surface of the electrothermal film to ensure safety during use.

[0058] Next, the sensor system was integrated: temperature and humidity sensors, a VOC sensor, and a temperature sensor for the electrothermal regeneration module were integrated into the floor structure. The temperature and humidity sensors have measurement ranges of 0-50℃ and 10%-90%RH, with accuracies of ±0.5℃ and ±3%RH, respectively; the VOC sensor has a detection range of 0.01-10ppm and a response time of 25 seconds; the temperature sensor monitors the operating temperature of the electrothermal regeneration module to ensure it remains within a safe range. The sensors communicate with the control unit via Bluetooth Low Energy (BLE) protocol.

[0059] Then, the system's structural design and assembly were carried out: a dedicated floor structure was designed, with a 4.5mm thick space reserved at the bottom of the substrate for installing the activated carbon fiber / graphene composite adsorption layer, electrothermal regeneration module, and sensor system. Each functional module was secured using a snap-fit ​​method, ensuring a compact structure without compromising the overall stability of the floor. Power and control lines were led out through pre-designed channels at the floor edges, connecting to an external control unit.

[0060] Finally, the control system and intelligent algorithm were developed: a microcontroller (MCU)-based control system was developed to collect sensor data and control the working status of the electrothermal regeneration module. The control algorithm includes: (1) pollutant concentration monitoring: when the VOC concentration exceeds 0.5 ppm for 30 minutes, the regeneration program is triggered; (2) intelligent regeneration control: the heat stored in the PCM is used for regeneration first, and when it is insufficient, the electrothermal module is activated to control the temperature within 60℃ for 45 minutes; (3) energy-saving mode: the regeneration program is executed when no one is around or during the night, according to the activity patterns of people in the room; (4) linkage control: linkage with the home ventilation system to increase ventilation during the regeneration process.

[0061] Example 1: Preparation of Bio-based Multi-component Composite Adhesive The preparation of bio-based multi-component composite adhesives includes four main steps: raw material pretreatment, composite adhesive preparation, adhesive modification and stabilization, and performance testing and adjustment.

[0062] First, raw material preparation and pretreatment were carried out: urea-formaldehyde resin (48% solid content), liquid sulfonated lignin (55% solid content), chitosan powder (molecular weight 300,000), and soy protein isolate (92% protein content) were pretreated separately. Specifically, the pH of the urea-formaldehyde resin was adjusted to 8.2 using sodium hydroxide solution; the liquid lignin was sulfonated to enhance its water solubility and activity; chitosan was dissolved in a 1.5% acetic acid solution to prepare a colloidal solution; and soy protein isolate was dissolved under alkaline conditions at pH 9.5 to open up the protein structure and expose more active sites.

[0063] The composite adhesive was then prepared: The pretreated components (urea-formaldehyde resin, lignin, chitosan, and soy protein isolate) were mixed in a reactor at a weight ratio of 50:14:4:28. The mixture was mechanically stirred at 250 rpm for 105 minutes at 65°C, with the pH maintained at 8.0 using sodium hydroxide solution. 0.8% ammonium chloride was added as a curing catalyst during the reaction, with the addition amount controlled to be 0.8% of the urea-formaldehyde resin mass.

[0064] Next, the adhesive was modified and stabilized: 4% polyfunctional isocyanate (MDI) was added to the reaction system as a crosslinking agent to strengthen the crosslinking network structure of the adhesive and improve water resistance and bonding strength. Simultaneously, 0.8% polyvinyl alcohol was added as a thickener and stabilizer to improve the rheological properties and storage stability of the adhesive. After thorough mixing, the reaction was continued at 65°C for 40 minutes to form a stable bio-based multi-component composite adhesive.

[0065] Finally, the adhesive performance was tested and adjusted: the tested adhesive had a solid content of 50%, a viscosity of 10000 mPa·s, a pH of 7.3, and a gel time of 75 seconds (at 100℃). The test results show that the prepared bio-based multi-component composite adhesive meets the process requirements for subsequent substrate preparation.

[0066] Example 2: Preparation and hot pressing of phase change energy storage temperature regulation substrate First, the fiber raw materials are prepared and processed: wood fiber (70%) and bamboo fiber (30%) are selected as the base material. The fiber raw materials are dried to control the moisture content within 4%. Through a screening process, particles with a fiber size of 0.5-2mm are selected to ensure uniform fiber size, which is beneficial for thorough mixing with the adhesive and the formation of a stable structure.

[0067] Then, microencapsulated phase change materials were prepared: n-alkane (eicosane C20H42) with a phase change temperature of 30℃ was selected as the core material, and microencapsulated phase change materials (MicroPCMs) were prepared by in-situ polymerization with polyurethane as the wall material. The average particle size of the microcapsules was controlled to be 15 μm, and the mass ratio of wall material to core material was 1:4.5 to ensure that the microcapsules had sufficient mechanical strength and thermal stability. The prepared MicroPCMs had a latent heat of phase change of 185 J / g and thermal stability that could withstand short-term heating at 190℃.

[0068] Next, the fiber material, adhesive, and phase change material were mixed: the treated fiber raw material was mixed with the bio-based multi-component composite adhesive prepared in Example 1 at a dry weight ratio of 9:1, and MicroPCMs were added at an amount of 10% of the total dry weight of the fiber and adhesive. The mixture was stirred in a high-speed mixer at 250 rpm for 12 minutes to ensure that the three materials were uniformly dispersed, forming a substrate blank containing PCMs.

[0069] Then, the substrate blank is pre-pressed and hot-pressed: the uniformly mixed substrate blank is pre-pressed at room temperature and a pressure of 2MPa for 2.5 minutes to form a pre-formed blank blanket. The pre-pressed blank blanket is then transferred to a hot press, using a segmented hot pressing process: for the first 5 minutes, the temperature is gradually increased to 175℃ and the pressure is 70% of the set value; for the next 10 minutes, the temperature is maintained at a constant 180℃ and the pressure at a constant 30MPa; for the last 3 minutes, the temperature is reduced to about 150℃ while maintaining full pressure, for a total hot pressing time of 18 minutes.

[0070] After hot pressing, the substrate board is transferred to a cooling rack, where forced air cooling is used to lower the temperature to below 40℃. The cooled board is then transferred to a humidity conditioning chamber and conditioned for 36 hours at 23℃ and 62% relative humidity to stabilize the moisture content at 8%.

[0071] Quality testing was conducted on the conditioned substrate, and the results showed that the density was 900 kg / m³. 3 The material exhibits a moisture content of 8%, a thickness expansion rate of 10.5% (after 24 hours of immersion), a static bending strength of 38 MPa, an internal bond strength of 0.65 MPa, and a formaldehyde release of 0.08 mg / L. Infrared thermal imaging confirmed that the PCMs are uniformly distributed within the substrate and exhibit consistent temperature control performance.

[0072] Example 3: Preparation of Multifunctional Wear-Resistant Layer and Composite Lamination of Flooring First, self-healing microcapsules were prepared: self-healing microcapsules containing dicyclopentadiene (DCPD) and Grubbs catalyst were prepared using interfacial polymerization. DCPD and Grubbs catalyst were mixed as the core material and dispersed in an aqueous phase to form an emulsion. Polyurethane prepolymer monomers were added to the core material emulsion, and a polyurethane wall material was formed on the surface of the core material through interfacial polymerization, resulting in self-healing microcapsules with an average particle size of 4 μm.

[0073] Then, the superhydrophobic nanomaterials were prepared: nano-sized silica particles (80 nm in diameter) were synthesized using the sol-gel method, and their surface was modified with perfluorotridecyltriethoxysilane to impart superhydrophobic properties. The modified nanoparticles had a water contact angle of 155° and an oil contact angle of 125°, exhibiting excellent antifouling and self-cleaning properties.

[0074] Next, a multifunctional UV-curable coating was formulated: aliphatic polyurethane acrylate as the main resin (65% of total solids), with the addition of 6% self-healing microcapsules, 3% superhydrophobic nanomaterials, and 5% tourmaline micropowder (2μm particle size). 4% nano-alumina was added as a wear-resistant reinforcing agent, 2.5% as a photoinitiator, and 1.5% as a leveling agent and defoamer. The mixture was thoroughly mixed using a high-speed disperser to prepare a UV-curable coating with a solids content of 96%.

[0075] The prepared UV-curable coating was evenly applied to the decorative paper, controlling the wet coating thickness to be 45 μm. Immediately after coating, the paper was placed in a UV curing system at UV-A (wavelength 365 nm, power density 350 mW / cm²). 2 It is cured under irradiation for 45 seconds to form a multifunctional wear-resistant layer with a thickness of 35μm.

[0076] A photocatalytic formaldehyde-capturing primer (containing 4% nano-titanium dioxide, 1.5% modified zeolite, and 2% activated carbon powder) was first coated onto the surface of the substrate prepared in Example 2, and dried at 65°C for 12 minutes to form a functionalized primer layer with a thickness of 28 μm. Then, decorative paper was precisely positioned on the functionalized substrate, and a multifunctional wear-resistant layer was placed over the decorative paper to form a laminated structure.

[0077] The laminated structure is transferred to a hot press, where it is heated in stages at a rate of 6°C / min to 160°C, and then hot-pressed for 4 minutes under a pressure of 4MPa. The temperature is then controlled to drop below 80°C before the pressure is released, resulting in low-formaldehyde reinforced composite wood flooring.

[0078] A comprehensive quality inspection of the finished flooring revealed the following results: surface abrasion resistance of 6500 revolutions, scratch resistance of 3.8N, stain resistance level 5, static bending strength of 38MPa, impact elasticity of 14%, and formaldehyde emission of 0.08mg / L. A self-healing scratch test was conducted under simulated usage conditions, showing that minor scratches (≤0.2mm wide) could self-heal within 24 hours, with a repair rate exceeding 85%. The water droplet contact angle test result was 152°, indicating that the flooring possesses excellent waterproof and stain-resistant properties.

[0079] Comparative Example 1: Preparation and Application of Traditional Urea-Formaldehyde Resin Adhesives Urea-formaldehyde resin adhesive was prepared using a traditional process: formaldehyde and urea were mixed at a molar ratio of 1.3:1 and reacted at 90°C for 60 minutes under conditions of pH 8.0-9.0 to induce hydroxymethylation. Then, the pH was adjusted to 4.5-5.5, and the temperature was lowered to 80°C for a condensation reaction for 40 minutes. Finally, the reaction was terminated by adjusting the pH to 7.5-8.0, yielding a urea-formaldehyde resin adhesive with a solid content of 50%.

[0080] The prepared urea-formaldehyde resin adhesive was mixed with wood fiber at a dry weight ratio of 1:8 and mixed in a high-speed mixer for 10 minutes to obtain a substrate blank. The blank was then hot-pressed at 190°C and 30MPa for 20 minutes to obtain a substrate board.

[0081] A common primer (without functional components) is applied to the surface of the substrate. After drying, decorative paper and a common wear-resistant layer (without self-healing microcapsules and superhydrophobic nanomaterials) are bonded together. The substrate is then hot-pressed at 170°C and 4MPa for 5 minutes to obtain traditional composite wood flooring.

[0082] Quality testing of the finished flooring showed the following results: surface abrasion resistance 4500 revolutions, scratch resistance 2.5N, stain resistance level 3, static bending strength 35MPa, impact elasticity 10%, and formaldehyde emission 0.28mg / L. The water droplet contact angle test result was 85°, indicating that the flooring's water and stain resistance is average. Scratch tests conducted under simulated usage conditions showed that minor scratches could not self-repair.

[0083] Comparative Example 2: Preparation and Application of Modified Urea-Formaldehyde Resin Adhesive (Non-Phase Change Material) Urea-formaldehyde resin adhesive was prepared using a modification process: formaldehyde and urea were mixed at a molar ratio of 1.2:1, and 5% lignin was added as a modifier. Hydroxymethylation was carried out at pH 8.2 and 85℃ for 70 minutes. Then, the pH was adjusted to 5.0, and the temperature was lowered to 75℃ for a condensation reaction for 45 minutes. Finally, the reaction was terminated by adjusting the pH to 7.8, yielding a modified urea-formaldehyde resin adhesive with a solid content of 50%.

[0084] The prepared modified urea-formaldehyde resin adhesive was mixed with wood fiber at a dry weight ratio of 1:8 and mixed in a high-speed mixer for 10 minutes to obtain a substrate blank (excluding phase change material). The blank was hot-pressed at 185°C and 30MPa for 18 minutes to obtain the substrate board.

[0085] A primer containing 1% formaldehyde scavenger is applied to the surface of the substrate. After drying, decorative paper and a regular wear-resistant layer are bonded together and hot-pressed at 165°C and 4MPa for 4 minutes to obtain modified composite wood flooring.

[0086] Quality testing of the finished flooring showed the following results: surface abrasion resistance 5000 revolutions, scratch resistance 3.0N, stain resistance level 4, static bending strength 36MPa, impact elasticity 12%, and formaldehyde emission 0.18mg / L. The water droplet contact angle test result was 90°, indicating that the flooring's water and stain resistance is average. Scratch tests conducted under simulated usage conditions showed that minor scratches could not self-repair. In indoor temperature fluctuation tests, the flooring surface temperature changed significantly with room temperature, indicating no temperature regulation function.

[0087] Comparative Example 3: Commercially available E0 grade composite wood flooring E0 grade composite wood flooring sold on the market was selected as a comparison sample. This product uses modified urea-formaldehyde resin as an adhesive, medium density fiberboard as the substrate, and melamine-impregnated paper as a decorative and wear-resistant layer on the surface.

[0088] Quality testing of the sample revealed the following results: surface abrasion resistance 5200 revolutions, scratch resistance 3.2N, stain resistance level 4, static bending strength 37MPa, impact elasticity 11%, and formaldehyde emission 0.15mg / L. The water droplet contact angle was 95°, indicating that the flooring's waterproof and stain-resistant performance is average. Scratch tests conducted under simulated usage conditions showed that minor scratches could not self-repair. In indoor temperature fluctuation tests, the flooring surface temperature changed significantly with room temperature, indicating a lack of temperature regulation functionality.

[0089] Performance Comparison Analysis of Examples and Comparative Examples To more intuitively demonstrate the differences between the present invention and conventional technology, a comparative analysis of the key performance indicators of Examples 1-3 and Comparative Examples 1-3 was conducted, and the results are shown in Table 1 below: Table 1

[0090] As can be seen from the table above, the reinforced composite wood flooring prepared by this invention outperforms traditional technologies in all performance indicators. Particularly in terms of formaldehyde emission, the product of this invention has an emission level of only 0.08 mg / L, far lower than the 0.28 mg / L of Comparative Example 1, and also significantly lower than the levels of Comparative Examples 2 and 3. Regarding surface properties, the abrasion resistance, scratch resistance, and stain resistance of the product of this invention are significantly superior to the comparative examples. Furthermore, the product of this invention possesses self-healing scratch capabilities, temperature regulation functions, and air purification functions—characteristics not found in traditional composite wood flooring.

[0091] To further verify the temperature regulation function of the product of the present invention, indoor temperature fluctuation tests were conducted on the flooring prepared in Example 2 and Comparative Example 2. During the process of the room temperature rising from 20°C to 30°C, the surface temperature of the flooring in Example 2 only increased by 7°C, while the surface temperature of the flooring in Comparative Example 2 increased by 9.5°C. This indicates that the product of the present invention has a significant temperature regulation effect, reducing the fluctuation range of the floor surface temperature by approximately 2.5°C.

[0092] Regarding air quality improvement, Example 3 and Comparative Example 3 were placed in an environment containing 0.5 mg / m³ of... 3 The formaldehyde concentration in the sealed space was tested for 24 hours. The results showed that the formaldehyde concentration in the space of Example 3 decreased by 85%, while the formaldehyde concentration in the space of Comparative Example 3 decreased by only 30%, proving that the product of the present invention has significant air purification capabilities.

[0093] In summary, the reinforced composite wood flooring prepared by this invention not only has excellent physical and mechanical properties and extremely low formaldehyde emission, but also possesses multiple functions such as scratch self-healing, temperature regulation, stain resistance and self-cleaning, and air purification, providing users with a healthier and more comfortable indoor environment. It has significant technical advantages and application value.

[0094] Through the detailed description of the above embodiments, those skilled in the art should understand that the present invention can be implemented in various forms and should not be limited to the specific implementation methods described in the above embodiments. The scope of protection of the present invention should be defined by the appended claims and their equivalents.

[0095] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

[0096] It should be noted that those skilled in the art can make various modifications and variations to this invention without departing from the spirit and scope of this invention. If such modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include such modifications and variations.

[0097] This disclosure also provides a computer-readable storage medium storing a computer program. When executed by a processor, the computer program performs the steps of a method for preparing reinforced composite wood flooring using a low-formaldehyde adhesive, as described in the above-described method embodiments. The storage medium can be either volatile or non-volatile computer-readable storage.

[0098] In addition, this disclosure also provides a computer program product, which stores a computer program. When the computer program is run by a processor, it executes the steps of any of the above-described methods for preparing reinforced composite wood flooring using low-formaldehyde adhesives. For details, please refer to the above-described method embodiments, which will not be repeated here.

[0099] The aforementioned computer program product can be implemented through hardware, software, or a combination thereof. In one optional embodiment, the computer program product is specifically embodied in a computer storage medium, which can be a volatile or non-volatile computer-readable storage medium. In another optional embodiment, the computer program product is specifically embodied in a software product, such as a software development kit (SDK), etc.

[0100] Those skilled in the art will clearly understand that, for the sake of convenience and brevity, the specific working processes of the devices and apparatuses described above can be referred to the corresponding processes in the foregoing method embodiments, and will not be repeated here. In the several embodiments provided in this disclosure, it should be understood that the disclosed devices, apparatuses, and methods can be implemented in other ways. The apparatus embodiments described above are merely illustrative. For example, the division of units is only a logical functional division, and in actual implementation, there may be other division methods. Furthermore, multiple units or components may be combined or integrated into another system, or some features may be ignored or not executed. Another point is that the displayed or discussed mutual coupling or direct coupling or communication connection may be through some communication interfaces; the indirect coupling or communication connection of devices or units may be electrical, mechanical, or other forms.

[0101] The units described as separate components may or may not be physically separate. The components shown as units may or may not be physical units; that is, they may be located in one place or distributed across multiple network units. Some or all of the units can be selected to achieve the purpose of this embodiment according to actual needs.

[0102] In addition, the functional units in the various embodiments of this disclosure can be integrated into one processing unit, or each unit can exist physically separately, or two or more units can be integrated into one unit.

[0103] If the aforementioned functions are implemented as software functional units and sold or used as independent products, they can be stored in a processor-executable, non-volatile, computer-readable storage medium. Based on this understanding, the technical solution of this disclosure, in essence, or the part that contributes to the prior art, or a portion of the technical solution, can be embodied in the form of a software product. This computer software product is stored in a storage medium and includes several instructions to cause a computer device (which may be a personal computer, server, or network device, etc.) to execute all or part of the steps of the methods described in the various embodiments of this disclosure. The aforementioned storage medium includes various media capable of storing program code, such as USB flash drives, portable hard drives, read-only memory (ROM), random access memory (RAM), magnetic disks, or optical disks.

[0104] Finally, it should be noted that the above-described embodiments are merely specific implementations of this disclosure, used to illustrate the technical solutions of this disclosure, and not to limit it. The protection scope of this disclosure is not limited thereto. Although this disclosure has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that any person skilled in the art can still modify or easily conceive of changes to the technical solutions described in the foregoing embodiments, or make equivalent substitutions for some of the technical features, within the scope of the technology disclosed in this disclosure; and these modifications, changes, or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this disclosure, and should all be covered within the protection scope of this disclosure. Therefore, the protection scope of this disclosure should be determined by the protection scope of the claims.

Claims

1. A method for preparing reinforced composite wood flooring using low-formaldehyde adhesive, characterized in that, Includes the following steps: Urea-formaldehyde resin, lignin, chitosan, and soy protein isolate are mixed and reacted at 60-70°C for 90-120 minutes to obtain a bio-based multi-component composite adhesive. The urea-formaldehyde resin is pre-adjusted to pH 8.0-8.5, the lignin is sulfonated, the chitosan is dissolved in a 1%-2% acetic acid solution to prepare a colloidal solution, and the soy protein isolate is dissolved under alkaline conditions at pH 9-10 to obtain pretreated components. These pretreated components include the pretreated urea-formaldehyde resin, Lignin, chitosan, and soy protein isolate; the pretreated components are mixed in a reactor at a weight ratio of 50:12-15:3-5:25-30 (urea-formaldehyde resin, lignin, chitosan, and soy protein isolate), and reacted by mechanical stirring at 200-300 rpm, maintaining the pH in the range of 7.5-8.

5. 0.5%-1% ammonium chloride is added as a curing catalyst to obtain a preliminary composite adhesive; 3%-5% polyfunctional isocyanate is added to the preliminary composite adhesive as a crosslinking agent and 0.Using 5%-1% polyvinyl alcohol as a stabilizer, the reaction is continued at 65℃ for 30-45 minutes to obtain the bio-based multi-component composite adhesive. Wood fiber and bamboo fiber are mixed with the bio-based multi-component composite adhesive at a dry weight ratio of 8:1-10:1, and microencapsulated phase change material is added. The mixture is then mixed using a high-speed mixer for 10-15 minutes to obtain a substrate blank containing phase change energy storage function. Specifically, n-alkanes with a phase change temperature of 28-32℃ are selected as the core material, and microencapsulation is performed using in-situ polymerization with polyurethane as the wall material. Microcapsules with an average particle size of 10-20 μm were prepared to obtain microencapsulated phase change materials. Based on the mixture of the bio-based multi-component composite adhesive and wood and bamboo fibers, the microencapsulated phase change material was added at a ratio of 8%-12% of the total dry weight of the fibers and adhesive, and mixed for 10-15 minutes using a high-speed mixer to obtain a substrate blank containing phase change energy storage function. The substrate blank was then subjected to segmented hot pressing at 175-185℃ and 28-32 MPa for 16-19 minutes to obtain the phase change energy storage material. Phase change energy storage temperature regulation substrate material; wherein, the substrate blank is preheated by gradually raising the temperature to 175°C and the pressure to 70% of the set value within the first 5 minutes to obtain a preheated blank; the preheated blank is then subjected to a main body hot pressing treatment at a constant temperature of 175-185°C and a constant pressure of 28-32MPa for the middle 9-12 minutes to obtain a preliminary shaped substrate; the preliminary shaped substrate is then cooled to 150°C and maintained at full pressure for shaping treatment within the last 2-3 minutes to obtain the phase change energy storage temperature regulation substrate material; the substrate material surface... A photocatalytic formaldehyde-capturing primer containing nano-titanium dioxide and modified zeolite is applied to the surface and dried to obtain a surface-functionalized substrate. A UV-curable coating containing self-healing microcapsules, superhydrophobic nanomaterials, and negative ion-releasing materials is applied to decorative paper and UV-cured to obtain a multifunctional wear-resistant layer. The surface-functionalized substrate, decorative paper, and multifunctional wear-resistant layer are then laminated and subjected to a second hot-pressing process at 155-165℃ and 3.5-4.5MPa for 3-5 minutes to obtain low-formaldehyde reinforced composite wood flooring.

2. The method according to claim 1, characterized in that, The photocatalytic formaldehyde-capturing primer comprises: using an aqueous polyurethane dispersion as a base material, adding 3%-5% nano titanium dioxide, 1%-2% modified zeolite and 1%-3% activated carbon micro powder, and adding 0.5%-1% silane coupling agent to prepare the photocatalytic formaldehyde-capturing primer with a solid content of 30%-35%.

3. The method according to claim 1, characterized in that, A UV-curable coating containing self-healing microcapsules, superhydrophobic nanomaterials, and negative ion releasing materials is applied to decorative paper and then UV-cured to obtain a multifunctional wear-resistant layer. The coating comprises: preparing self-healing microcapsules with an average particle size of 3-5 μm using dicyclopentadiene as the core material and polyurethane as the wall material via interfacial polymerization to obtain a self-healing component; synthesizing nano-silica particles with a particle size of 50-100 nm using a sol-gel method, and obtaining superhydrophobic nanomaterials through surface modification with perfluorotridecyltriethoxysilane; adding 5%-8% of the self-healing component, 2%-4% of the superhydrophobic nanomaterials, 4%-6% of tourmaline micropowder, and 3%-5% of nano-alumina, along with 2%-3% of a photoinitiator, based on an aliphatic polyurethane acrylate main resin to obtain a UV-curable coating containing multifunctional components; applying the UV-curable coating containing multifunctional components to decorative paper, controlling the wet coating thickness to 40-50 μm, and applying the coating at a wavelength of 365 nm and a power density of 300-400 mW / cm². 2 The multifunctional wear-resistant layer is cured under UV-A irradiation for 30-60 seconds to obtain a pre-cured multifunctional wear-resistant layer; the thickness of the pre-cured multifunctional wear-resistant layer is controlled to ensure that the final thickness is 30-40μm, thus obtaining the multifunctional wear-resistant layer.

4. The method according to claim 3, characterized in that, The self-healing microcapsules are prepared by interfacial polymerization, comprising: mixing the dicyclopentadiene with a Grubbs catalyst as a core material and dispersing it in an aqueous phase to form an emulsion, thereby obtaining a core material emulsion; adding a polyurethane prepolymer monomer to the core material emulsion and forming a polyurethane wall material on the surface of the core material through an interfacial polymerization reaction, thereby obtaining the self-healing microcapsules.

5. The method according to claim 1, characterized in that, The surface-functionalized substrate is laminated with decorative paper and the multifunctional wear-resistant layer, and then subjected to a second hot-pressing process for 3-5 minutes at a temperature of 155-165℃ and a pressure of 3.5-4.5MPa. This process includes: precisely positioning the decorative paper on the surface-functionalized substrate, covering the decorative paper with the multifunctional wear-resistant layer to form a laminated structure, and obtaining a pre-laminated body; the pre-laminated body is heated in stages at a rate of 5-8℃ / min to 155-165℃ and held under pressure, and then cooled to below 80℃ before depressurization to obtain the low-formaldehyde reinforced composite wood flooring.

6. The method according to claim 1, characterized in that, Also includes: Integrate active environment regulation functions into the low-formaldehyde laminated composite wood floor: select activated carbon fiber felt with a specific surface area ≥1500m 2 / g, grow graphene nanosheets on its surface by chemical vapor deposition to obtain an activated carbon fiber / graphene composite adsorption layer; based on the conductive properties of the activated carbon fiber / graphene composite adsorption layer, print carbon nanotube conductive ink on a polyimide film substrate to form a matching electrothermal film with a controlled sheet resistance of 10-20Ω, to obtain an electrothermal regeneration module; based on the working requirements of the electrothermal regeneration module, integrate temperature and humidity sensors, VOC sensors and temperature sensors, and communicate with the control unit through the low-power Bluetooth protocol to obtain a sensor system matched with the regeneration module; take the activated carbon fiber / graphene composite adsorption layer, the electrothermal regeneration module and the sensor system as an integrated functional module, install it in the reserved space at the bottom of the substrate of the low-formaldehyde laminated composite wood floor, to obtain a laminated composite wood floor with active environment regulation functions.

Citation Information

Patent Citations

  • Process of making moistureproof health wooden floor board with self-cleaning function

    CN101020331A

  • Phase change heat-storage thermoregulation polymerization wooden plate

    CN101085550A

  • Hydrophobic heat-conducting self-repairing composite coating and preparation method thereof

    CN119549375A